Kajian Kesiapan Pemerintah Daerah Kabupaten Batang Dalam Menghadapi Proyek Strategis Nasional (PSN) Kawasan Industri Terpadu (KIT) Batang - Satya Budi Nugraha; Ananto Aji; Husna Fauzia (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
The Batang Integrated Industrial Estate (KIT Batang) development is one of the National Strategic Projects (PSN) stipulated by Presidential Regulation. This project is in line with the spatial planning objective of Batang Regency, namely the realization of Regency space that has an attractiveness for investment in the industrial sector. This study aims to analyze the readiness of the Regional Government of Batang Regency in terms of policy, institutional, financial, facilities, and infrastructure aspects in dealing with the PSN for the Batang Integrated Industrial Estate. Data was collected by using literature study and interview methods. Furthermore, the data and information obtained were analyzed by descriptive methods and scoring analysis. Regional readiness criteria are assessed based on the calculation of scores in the categories of not ready, quite ready, ready, and very ready. The results showed that the Regional Government (Pemda) of Batang Regency was included in being very ready to welcome PSN KIT Batang. Policies at the regional level show a good and fast response from the local government to national policies. Likewise, in preparing spatial planning programs around the Batang KIT, infrastructure development and budget allocations have been planned quickly and programmed so that the current Batang KIT development process runs smoothly. Furthermore, the Batang local government needs to facilitate the improvement of the educational qualifications and skills of the community so that in time they have competencies that follow the needs of workers in the industrial sector.